GranDGamesBR: Perceptual Analysis of Computer Graphics Characters in Digital Entertainment - Musse, Soraia Raupp; Pinho, Greice; Dalmoro, Bruna; Araujo, Victor Flávio de Andrade (Anais Estendidos do Simpósio Brasileiro de Jogos e Entretenimento Digital (SBGames); 2021: Anais Estendidos do XX Simpósio Brasileiro de Jogos e Entretenimento Digital, 2021)
This paper presents a discussion regarding the area of perceptual analysis in Computer Graphics characters. This discussion is focused on presenting one challenge area in Digital Entertainment. Many issues in the area of perception analysis have been researched in last years, in particular with respect to the theory of Uncanny Valley (UV) proposed by Masahiro Mori in 1970. Indeed, it is known that realistic characters from movies and games can cause strangeness and involuntary feelings in viewers, what can affect the acceptance of audience in games and movies. This paper aims to present concepts and discuss issues in this area.